Analysis on Cooling Effect of Crushed-Rocks Embankment of Qinghai-Tibet High-Grade Road. (12th March 2015) - Li, Dongqing; Zhang, Kun; Tong, Gangqiang; Ming, Feng; Huang, Xing
Abstract : In order to study the cooling effect of the crushed-rocks embankment, the permeability and the inertial resistance coefficient were measured by the wind tunnel test of spheres with a diameter of 20 cm, and then the stabilities of the closed crushed-rocks embankment with the wide pavement, the closed crushed-rocks embankment with the narrow pavement, and the duct-ventilated and closed crushed-rocks embankment were calculated. In the next 50 years, assuming that the temperature in Qinghai-Tibet plateau will rise by 2.6°C condition, the cooling effects of these three special high-grade embankment structures were studied. The test results and the numerical calculation results show that the relationship between pressure gradient and seepage velocity in the spheres layer diverges completely from Darcy's law, and it shows a nice quadratic nonlinear relationship. Stabilities of those two closed crushed-rock embankments without the duct-ventilated structure could be destroyed because of the high permafrost temperature under embankments. The duct-ventilated and closed crushed-rocks embankment can cool down the permafrost effectively and raise the permafrost table and ensure the long-term thermal stability of permafrost under road.